Ultrasound monitoring of microcirculation: An original study from the laboratory bench to the clinic. (29th June 2022) - Aghabaglou, Fariba; Ainechi, Ana; Abramson, Haley; Curry, Eli; Kaovasia, Tarana Parvez; Kamal, Serene; Acord, Molly; Mahapatra, Smruti; Pustavoitau, Aliaksei; Smith, Beth; Azadi, Javad; Son, Jennifer K.; et al.
Abstract: Objective: Monitoring microcirculation and visualizing microvasculature are critical for providing diagnosis to medical professionals and guiding clinical interventions. Ultrasound provides a medium for monitoring and visualization; however, there are challenges due to the complex microscale geometry of the vasculature and difficulties associated with quantifying perfusion. Here, we studied established and state‐of‐the‐art ultrasonic modalities (using six probes) to compare their detection of slow flow in small microvasculature. Methods: Five ultrasonic modalities were studied: grayscale, color Doppler, power Doppler, superb microvascular imaging (SMI), and microflow imaging (MFI), using six linear probes across two ultrasound scanners. Image readability was blindly scored by radiologists and quantified for evaluation. Vasculature visualization was investigated both in vitro (resolution and flow characterization) and in vivo (fingertip microvasculature detection). Results: Superb Microvascular Imaging (SMI) and Micro Flow Imaging (MFI) modalities provided superior images when compared with conventional ultrasound imaging modalities both in vitro and in vivo. The choice of probe played a significant difference in detectability. The slowest flow detected (in the lab) was 0.1885 ml/s and small microvasculature of the fingertip were visualized. Conclusions: Our data demonstrated that SMI and MFI used with vascular probes operating at higher frequencies provided resolutions acceptable for microvasculature visualization, paving the path for future development of ultrasound devices for microcirculation monitoring.